Adolescents' Attitudes Toward Same-Sex Marriage and Adoption in France. Issue 1 (1st January 2016) - Vecho, Olivier; Paul Poteat, V.; Schneider, Benoit
Abstract: Research on attitudes toward sexual minority rights has predominantly focused on adults within the United States. Adolescents' positions have been neglected, yet they will have a major influence on future policies for sexual minorities. To extend previous research, this study examined 405 French high school students' views toward same-sex marriage (SSM) and same-sex adoption (SSA), while testing factors (homophobia, social dominance orientation [SDO], empathic concern, and perspective taking) that could account for variability in these views. Results indicated that females were more supportive than males on SSM and SSA, and that both were more in favor of SSM than SSA. Controlling for age, gender, and socially desirable responding, mediation tests revealed that the effects of SDO and perspective taking on SSM and SSA positions were mediated through beliefs about lesbian and gay individuals, but not through feelings toward lesbian and gay individuals. Empathic concern did not account for SSM and SSA over and above these other factors. Implications for future research in this area are discussed.